Kompilasi Hukum Islam dan Rancangan Undang-Undang RI tentang Hukum Terapan Peradilan Agama - Amir Mu'allim (Universitas Islam Indonesia, 2003)
It is clearly proved that the Compilation of Islamic law which was issued by the Presidential Decree no.1/1991 is not far from weaknesses. The weaknesses appear in some chapters and articles, such as in the articles on marriage. Indeed, the content also shows contradiction with other regulations. Therefore, the effort to issue the regulation on the Implementation of Islamic Law (Undang-Undang Terapan) must be strongly supported due to the need for creating better implementation of Islamic legal system in Indonesia.